A low-smoke, halogen-free, flame-retardant ABS material for edge banding and preparation method thereof
By compounding emulsion copolymer with bulk ABS, combining silicone rubber and modified graphene to load halogen-free flame retardants, and using flame retardants and smoke suppressants collaboratively, the deficiencies in heat resistance and flame retardant properties of ABS materials are solved. problem, achieving high strength, high toughness and good flame retardant properties of the material.
Patent Information
- Application Number
- CN202411314471.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing ABS resin materials have poor heat resistance in extreme cases and have poor flame retardant properties. The added flame retardant affects the weather resistance of the material, resulting in a shortened service life and produces harmful gases during combustion.
The emulsion -type cluster is obtained through the emulsion method and the ontology method ABS is reproduced. The silicon rubber is added as a tougin agent. Magnesium and magnesium cobalt-in-nitrate nitrate can be cigarettes through nuclear-crystal isolation, and graphene load-free flame-free flame retardants are treated by KH-570 modified.
The stretching strength, impact strength and low temperature resistance of ABS materials have been improved, and at the same time, it significantly improves the flame retardant performance and thermal resistance of the material. The total amount of smoke release is reduced, and the residual charcoal rate is increased.
Smart Images

Figure CN118852835B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, in particular to a low-smoke halogen-free flame retardant ABS material for edge banding and a preparation method thereof. Background Art
[0002] ABS resin plastic is the polymer with the largest output and the most widely used today. It has good physical and mechanical properties, high impact strength, good chemical stability and electrical properties, good finished product processing and mechanical processing performance, and is resistant to water, inorganic salts, acids and alkalis. It is a widely used engineering material. However, the current ABS resin still has the disadvantages of low mechanical strength, weak heat resistance in extreme cases, poor flame retardancy, and a large amount of smoke generated during combustion, which limits its application range.
[0003] Since the limiting oxygen index of ABS resin is only 18.3%-20%, it is a flammable polymer material. When it is used in various electronic and electrical products with flame retardant requirements, it needs to be flame-retardant modified to meet the safety and fire protection requirements. At present, the most mature and effective flame retardant modification method for ABS is to add bromine flame retardants and antimony flame retardants. However, the addition of flame retardants affects the weather resistance of the material and easily causes premature aging of important components such as battery casings, thereby shortening the service life. At the same time, the addition of halogen flame retardants produces a large amount of harmful gases during the combustion process, further polluting the environment.
[0004] Patent CN101591468B discloses a low-smoke halogen-free flame-retardant PC / ABS alloy and a preparation method thereof. Polycarbonate, ABS, composite flame retardant, composite smoke reducer, compatibilizer, low-smoke promoter, stabilizer, and lubricant are weighed by weight percentage. The prepared PC / ABS alloy has the characteristics of low smoke emission, halogen-free flame retardancy, and excellent comprehensive performance, but its heat resistance is not ideal. At the same time, the smoke emission is about 600, which needs to be further reduced.
[0005] Patent CN114292488B reports an anti-stick and oil-resistant ABS alloy material, its preparation method and use. By using an anti-stick agent and nano-montmorillonite, a lubricating layer is formed on the ABS alloy material during heating and melting welding to prevent the carbonization of the ABS alloy material caused by long-term bonding in the hot melt state. However, the introduction of rigid groups into PBT can easily lead to deterioration of the material's tensile and impact properties, and reduce its mechanical properties.
[0006] Patent CN116694018B reports a halogen-free flame retardant modified ABS plastic and its synthesis process, using nitrogen-phosphorus styrene-acrylonitrile copolymer as a halogen-free flame retardant to compound with ABS resin to obtain halogen-free flame retardant modified ABS, but the resulting ABS material has poor thermal stability, which limits its application in high-temperature fields.
[0007] Patent CN114805936A discloses a flame retardant suitable for ABS resin, a preparation method thereof, and a flame retardant ABS resin. The ABS resin is prepared by using 2-carboxyethylphenylphosphite amide coated with a surface polymer, a thermoplastic phenolic resin, and an inorganic salt, which effectively solves the problem that the ABS resin cannot simultaneously take into account the mechanical properties and flame retardant properties of the material; however, the volatilization temperature of the 2-carboxyethylphenylphosphite amide is lower than the processing temperature of the ABS alloy, and it is easy to volatilize and ooze out during the processing, and it has a high volatility, which reduces the flame retardant properties of the ABS resin.
[0008] Therefore, a low-smoke, halogen-free, flame-retardant ABS material for edge banding and a preparation method thereof are proposed. Summary of the invention
[0009] The invention aims to provide a low-smoke halogen-free flame-retardant ABS material for edge banding and a preparation method thereof. An emulsion-type copolymer is prepared by an emulsion method and compounded with a bulk ABS, the proportions of the bulk ABS and the emulsion-type copolymer are controlled, and the tensile strength of the ABS material is increased; silicone rubber is added as a toughening agent to improve the compatibility of the material and the impact strength of the material, and the introduction of silicone rubber improves the low-temperature resistance of the material; benzoxazine flame retardants have good carbonization properties and can be synergistically involved in the flame retardant process with organic phosphorus flame retardants to increase the flame retardancy of ABS; cobalt nitrate hexahydrate and magnesium nitrate hexahydrate are used to prepare a smoke suppressant by a nucleation-crystallization isolation method, the crystallinity and dosage of the smoke suppressant are controlled, and the total smoke release of the material is increased; graphene is modified by KH-570, and the halogen-free flame retardant is loaded in the structure, so as to increase the compatibility and improve the heat resistance and residual carbon rate of the material.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] In one aspect, the present invention provides a method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding, the method comprising the following steps:
[0012] 20-40 parts of emulsion copolymer, 70-100 parts of bulk ABS, graphene-loaded halogen-free flame retardant, 10-25 parts of toughening agent, 2 parts of antioxidant 1010, and 2-10 parts of smoke suppressant are placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dry material; the dry material is added to a high-speed mixer and stirred at 500r / min for 30 minutes, and mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain pellets; the pellets are vacuum dried at 85°C for 5 hours and then injection molded by an injection molding machine to obtain a halogen-free flame-retardant ABS material;
[0013] The emulsion copolymer is prepared by emulsifying isoprene, styrene and acrylonitrile in a ratio of 17:61:22;
[0014] The smoke suppressant is prepared by a nucleation-crystallization isolation method using a cobalt nitrate hexahydrate solution and a magnesium nitrate hexahydrate solution;
[0015] The graphene-loaded halogen-free flame retardant is prepared by dispersing 5-15 parts of modified graphene and 8-18 parts of halogen-free flame retardant in anhydrous ethanol, and stirring and reacting at 80° C. for 2 hours.
[0016] The modified graphene is prepared by acidifying graphene and modifying it with a silane coupling agent;
[0017] The halogen-free flame retardant comprises a flame retardant 1 and a flame retardant 2, which are mixed in a ratio of 1-3:1-3.
[0018] Preferably, the bulk ABS is selected from one of ABS 8391, ABS 3504, ABS 8434, and ABS 275.
[0019] Preferably, the toughening agent is selected from one of styrene-butadiene-styrene block copolymer, ethylene-vinyl acetate copolymer, styrene-butadiene rubber, butadiene rubber, and silicone rubber.
[0020] Preferably, the flame retardant 1 is selected from one of benzoxazine flame retardants, polyvinyl chloride, polyphenylene ether, and phenolic resin; the flame retardant 2 is selected from one of triphenyl phosphate, ammonium metaphosphate, and resorcinol.
[0021] Preferably, the preparation method of the benzoxazine flame retardant comprises the following steps:
[0022] Aniline, 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene and polyformaldehyde are stirred and mixed in a beaker at room temperature to obtain a mixed solution; 1 / 10 of the mixed solution is added to a 1000 ml flask, the temperature is raised to 70°C, and the reaction is carried out for 10 minutes to obtain a reaction solution 1; 1 / 10 of the second batch of the mixed solution is added to the reaction solution 1, and the reaction is carried out for 10 minutes to obtain a reaction solution 2; the remaining mixed solution is added, and after the raw materials are added, the reaction temperature is maintained at 110°C, and the reaction is carried out under reflux for 20 minutes to obtain a reaction system; the reaction system is heated to 130°C, stirred and refluxed for 30 minutes to evaporate water, centrifuged, and vacuum dried at 80°C for 2 hours to obtain the benzoxazine flame retardant.
[0023] Preferably, the preparation method of the smoke suppressant comprises the following steps:
[0024] Prepare a cobalt nitrate hexahydrate solution and a magnesium nitrate hexahydrate solution, add them to a flask and stir evenly to obtain a mixed metal solution; prepare a sodium hydroxide solution and a sodium carbonate solution, add them to a flask, stir evenly to obtain a mixed alkali solution; slowly add the mixed metal solution and an equal volume of the mixed alkali solution into a rotating liquid film reactor at a speed of 3000 rpm, stir for 20 minutes to obtain a nucleation slurry; transfer the nucleation slurry to a flask, heat to 100°C and reflux for 6 hours to obtain a reactant; wash the reactant with deionized water, rinse with ethanol, adjust the pH to neutral, and vacuum dry at 60°C for 24 hours to obtain the smoke suppressant.
[0025] Preferably, the molar ratio of the cobalt nitrate hexahydrate solution to the magnesium nitrate hexahydrate solution is 1-4:1-2.
[0026] Preferably, the method for preparing the graphene-loaded halogen-free flame retardant comprises the following steps:
[0027] The graphene is placed in a muffle furnace and calcined for 5 hours to obtain fired graphene; the fired graphene is added to a 10% hydrochloric acid solution and heated to reflux at 50°C for 10 hours, centrifuged and washed, and freeze-dried to obtain acidified graphene; the acidified graphene is added to a three-necked flask, dissolved in a mixed solution of ethanol and water to obtain a mixed solution, the mixed solution is adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, a silane coupling agent is added, and the mixture is stirred and reacted for 6 hours in a water bath at 85°C to obtain modified graphene; the modified graphene is placed in a beaker, anhydrous ethanol is added, stirred and dispersed evenly, to obtain a dispersion; the halogen-free flame retardant is added to the dispersion, and the dispersion is transferred to a reactor and stirred and reacted at 80°C for 2 hours, separated and centrifuged, and vacuum dried to obtain the graphene-loaded halogen-free flame retardant.
[0028] Preferably, the operating parameters of the twin-screw extruder are a screw speed of 280 r / min, a feed speed of 30 r / min, temperatures from the first temperature zone to the eighth temperature zone are: 200°C, 205°C, 210°C, 215°C, 220°C, 220°C, 215°C, 210°C, and the head temperature is 205°C.
[0029] Preferably, the working parameters of the injection molding machine are that the temperatures of zone one to zone three are 205°C, 210°C, and 220°C respectively, the nozzle temperature is 210°C; the holding time is 15s, the cooling time is 20s, the holding pressure is 120MPa, the injection temperature is 200°C-220°C, and the injection pressure is 40%-60% of the maximum pressure.
[0030] Preferably, the silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0031] On the other hand, the present invention provides a low-smoke halogen-free flame-retardant ABS material for edge banding strips, wherein the low-smoke halogen-free flame-retardant ABS material comprises an emulsion copolymer, a bulk ABS, modified graphene, a halogen-free flame retardant, a toughening agent, an antioxidant 1010, and a smoke suppressant; the low-smoke halogen-free flame-retardant ABS material is prepared by any of the preparation methods described above; the tensile strength of the ABS material is 55MPa, and the elongation at break is 31.5%; the room temperature impact strength of the ABS material is 33.2KJ / m2, and the low temperature impact strength is 15.8KJ / m2; the limiting oxygen index of the ABS material is 35.6%; the total smoke release of the ABS material is 8.5m2; the initial decomposition temperature of the ABS material is 364°C, and the residual carbon rate is 51.2%.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention uses an emulsion copolymer prepared by an emulsion method and compounded with bulk ABS. Compounding two ABS with different rubber phase particle sizes can improve the elongation at break of the ABS material and has little effect on the tensile strength. ABS 8391 is used to compound with the emulsion copolymer, and the proportions of bulk ABS and the emulsion copolymer are controlled. The tensile strength of the prepared ABS material is 55 MPa, and the elongation at break is 31.5%.
[0034] 2. The present invention improves the compatibility of the base material and the processing aid in the ABS material by adding a toughening agent. At the same time, the addition of the toughening agent can increase the compatibility between molecules in the ABS material system, which can induce silver streaks and shear bands. The generation and development of silver streaks and shear bands consume a lot of energy. The room temperature impact strength of the prepared ABS material is 33.2KJ / m 2 , low temperature impact strength is 15.8KJ / m 2 , good low temperature resistance and high impact strength.
[0035] 3. The present invention uses graphene to load halogen-free flame retardants, controls the type and amount of halogen-free flame retardants, and utilizes the good carbonization property of BOZ to cooperate with organic phosphorus flame retardants in the flame retardant process; the limiting oxygen index of the obtained ABS material is 35.6%, which has significantly improved flame retardant properties.
[0036] 4. The present invention uses cobalt nitrate hexahydrate and magnesium nitrate hexahydrate to prepare a smoke suppressant through a nucleation-crystallization isolation method. By controlling the molar ratio of the metal solution, the crystallinity of the smoke suppressant is controlled. Due to the reduced crystallinity, agglomeration is likely to occur, resulting in a rough surface, reducing its dispersibility in the ABS material, and increasing the total amount of smoke released. By controlling the molar ratio of the metal solution and the amount of the smoke suppressant, the smoke density of the prepared ABS material is 235, and the smoke release is reduced.
[0037] 5. The present invention uses graphene modified by silane coupling agent to load halogen-free flame retardant to avoid decomposition of halogen-free flame retardant due to excessively high temperature during combustion, thereby reducing the flame retardant performance of the material. At the same time, the modification of silane coupling agent increases the compatibility of graphene with ABS material, and graphene is evenly dispersed in the material matrix, thereby increasing the heat resistance of ABS. The initial decomposition temperature of the obtained low-smoke halogen-free flame retardant ABS material is 364°C, and the residual carbon rate is 51.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM surface morphology image of the smoke suppressant prepared in Example 37;
[0039] Figure 2 It is a graph showing the change in initial decomposition temperature and residual carbon rate of Example 49 and Examples 51-54. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The SBS described in the present invention is a styrene-butadiene-styrene block copolymer.
[0042] The EVA described in the present invention is ethylene-vinyl acetate copolymer.
[0043] The KH-550 described in the present invention is 3-aminopropyltriethoxysilane, CAS: 919-30-2.
[0044] The KH-560 described in the present invention is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, CAS: 2530-83-8.
[0045] The KH-570 described in the present invention is methacryloxypropyltriethoxysilane, CAS: 2530-85-0.
[0046] The KH-792 described in the present invention is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, CAS: 1760-24-3.
[0047] The BOZ described in the present invention is a benzoxazine flame retardant.
[0048] The TPP described in the present invention is triphenyl phosphate, CAS: 115-86-6, purchased from Anhui Zesheng Technology Co., Ltd.
[0049] The PVC described in the present invention is polyvinyl chloride, which is purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0050] The PPO described in the present invention is polyphenylene ether purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0051] The PFR described in the present invention is phenolic resin purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0052] See also Figure 1 to Figure 2 The present invention provides a low-smoke, halogen-free, flame-retardant ABS material for edge banding and a preparation method thereof. The technical scheme is as follows: Example 1
[0053] 20 parts of deionized water, 17 parts of isoprene, 0.3 parts of rosin soap solution and 0.2 parts of potassium persulfate are added to an autoclave, and nitrogen is replaced to obtain a reaction solution; the reaction solution is heated to 65°C, and polymerization reaction is carried out at 200rpm for 5 hours to obtain rubber latex; the rubber latex is added to a reactor, the temperature is raised to 65°C, and stirring is performed to mix uniformly to obtain a reaction raw material; 61 parts of styrene and 22 parts of acrylonitrile, 2 parts of tert-dodecyl mercaptan and 1.5 parts of cumene hydroperoxide are added to the reaction raw material within 1 hour, and the reaction is kept warm for 2 hours to obtain a reaction system; 0.5 parts of cumene hydroperoxide are added to the reaction system, and the reaction is kept warm for 0.5 hours to obtain an ABS emulsion; the ABS emulsion is subjected to demulsification, separation and centrifugation, and vacuum drying at 60°C for 2 hours to obtain an emulsion copolymer;
[0054] The emulsion copolymer, bulk ABS, and graphene-loaded halogen-free flame retardant, including 10 parts of modified graphene, 15 parts of halogen-free flame retardant, 18 parts of silicone rubber, 2 parts of antioxidant 1010, and 5 parts of smoke suppressant, are placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dry material; the dry material is added into a high-speed mixer and stirred at 500 r / min for 30 minutes to obtain a mixture; the mixture is added into a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain pellets; the pellets are vacuum dried at 85°C for 5 hours and then injection molded by an injection molding machine to obtain a low-smoke halogen-free flame retardant ABS material.
[0055] Example 2-11 The preparation method and parameter conditions of Example 1 are referred to, and the differences are shown in Table 1.
[0056] Comparative Example 1 The preparation method and parameter conditions are the same as those of Example 1, except that no bulk ABS is added and only the emulsion copolymer is used.
[0057] Comparative Example 2 The preparation method and parameter conditions of Example 1 are referred to, except that no emulsion copolymer is added and only bulk ABS is used.
[0058] Example 12 Tensile Properties Test
[0059] The ABS materials prepared in Examples 2-11 and Comparative Examples 1-2 were tested for tensile strength and elongation at break using a universal testing machine; tensile strength: tested according to ISO527-2-2012, with a tensile speed of 50 mm / min; elongation at break: tested according to ISO527-2-2012, with a tensile speed of 10 mm / min, and the results are shown in Table 1.
[0060] Table 1 Tensile performance test of Examples 2-11 and Comparative Examples 1-2
[0061]
[0062] From the results in Table 1, it can be seen that the tensile strength and elongation at break of the ABS materials prepared by using bulk ABS or emulsion copolymer in Comparative Examples 1-2 cannot be taken into account at the same time; in Comparative Example 2, since the bulk ABS has less residual monomers, better thermal stability, larger particle size, and stronger intermolecular forces, it shows high tensile strength, but the elongation at break is only 8.2%; in Comparative Example 1, only the emulsion copolymer is used, due to the increase of isoprene content, enhanced molecular flexibility, dispersed intermolecular forces, increased elongation at break, but relatively reduced tensile strength; From the results of Examples 1-4, it can be seen that the tensile strength and elongation at break of the ABS materials prepared by using bulk ABS or emulsion copolymer in Comparative Example 1 are not both good and bad; It is known that with the addition of bulk ABS, the elongation at break of ABS material increases significantly; with the increase of bulk ABS rubber particle size, the tensile strength of the resin changes little, and the elongation at break first decreases and then increases. When the particle size is large, the intermolecular hydrogen bond effect is weak, the intermolecular force is low, and more energy cannot be absorbed during the stretching process. With the decrease of the rubber phase particle size, the intermolecular force increases, the flexible group buffers the energy, and the elongation at break increases. When the particle size is too large, the compatibility with the material additives is reduced, the force is weakened, and the impact performance is reduced. Comparative Example 1, Implementation From the results of Examples 5-8, it can be seen that with the increase in the amount of the main ABS, the tensile strength of the composite resin increases slowly, and the change is not obvious. The elongation at break shows a trend of first increasing and then tending to be constant with the increase in the amount. Since the emulsion copolymer has good gloss and a small rubber particle size, compounding two ABS with different rubber particle sizes can improve the elongation at break of the ABS material, and has little effect on the tensile strength. At the same time, when the amount of the main ABS is too large, the emulsion copolymer with a small particle size is easy to fall into the cracks of the resin, preventing the development of silver streaks and reducing the impact performance. From the results of Examples 1 and 9-11, it can be seen that with the slow decrease in the tensile strength of the emulsion copolymer content, the elongation at break shows a trend of first increasing and then decreasing. Since ABS has a large deformation before breaking, the cross section is epitaxially deformed when breaking, which can consume more energy, so that the material has enhanced impact resistance. When subjected to a large load, it first absorbs energy through plastic deformation. The emulsion copolymer provides more rubber phase, prevents the rapid consumption of energy, increases energy transfer, and disperses energy evenly. However, excessive amounts lead to reduced energy transfer, and the absorbed energy is insufficient to support plastic deformation. From the results in Table 1, it can be seen that by compounding ABS 8391 with emulsion copolymer and controlling the proportion of bulk ABS and emulsion copolymer, the tensile strength of the prepared ABS material is 55 MPa and the elongation at break is 31.5%, which has significantly improved tensile properties.
[0063] Examples 13-21 The preparation methods and parameter conditions of Example 1 are referred to, with the differences shown in Table 2.
[0064] Comparative Example 3 The preparation method and parameter conditions are the same as those of Example 1, except that no toughening agent is added.
[0065] Example 22 Impact performance test
[0066] The halogen-free flame-retardant ABS materials prepared in Examples 13-21 and Comparative Example 3 were tested for notched impact strength using a notched impact testing machine (Shenzhen Sansi Zongheng Technology Co., Ltd.), and the notched impact strength at room temperature and low temperature was tested respectively with reference to ISO179-1 standard; the room temperature condition was 23±2°C; the low temperature condition was -30±2°C, and the materials were placed for 6 hours, and then the notched impact strength was tested at -30°C. The specific results are shown in Table 2.
[0067] Table 2 Impact strength test of Examples 13-21 and Comparative Example 3
[0068]
[0069] From the results in Table 2, it can be seen that the room temperature impact strength and low temperature impact strength of the halogen-free flame retardant ABS prepared without adding a toughening agent in Comparative Example 3 are significantly reduced compared with Examples 13-21. The addition of a toughening agent can increase the compatibility between molecules in the ABS material system, and can induce silver streaks and shear bands. The generation and development of silver streaks and shear bands consume a lot of energy, which improves the toughness of the ABS material. The results of Examples 13-17 show that compared with rubber toughening agents, since EVA is a flexible polymer, its own impact strength is very low, and the weak mechanical strength offsets the toughening effect of EVA, resulting in a decrease in the impact strength of the ABS material. The use of SBS increases the compatibility of the ABS material and increases the impact strength. However, under low temperature conditions, the large number of rigid groups contained in SBS increase brittleness and are prone to brittle fracture; the use of rubber toughening agents can reduce the effect of temperature on the material, and the excellent low temperature resistance of silicone rubber improves the impact strength of the material. Strength, while giving ABS material low temperature resistance; the results of Example 13 and Examples 18-21 show that with the increase of the amount of toughening agent, the low temperature impact strength of ABS material shows a trend of first increasing and then decreasing. Since silicone rubber has good softness and elasticity, the flexibility between the chain segments of ABS material increases. Excessive toughening agent makes the molecular chain of ABS material easy to stretch when subjected to external force, and the chain segments are easy to slip against each other, thereby causing the low temperature impact strength of ABS material to decrease, but the room temperature impact strength gradually increases. When the amount exceeds a certain level, the impact strength increase trend slows down. If the amount of silicone rubber continues to increase, the silver grain branching and shear band effect of the rubber particles reach saturation, and the toughening effect gradually slows down. In addition, excessive silicone rubber will reduce the compatibility of ABS with flame retardants, resulting in a decrease in flame retardant properties; Comprehensive Table 2 results show that by changing the type and amount of toughening agent, the room temperature impact strength of the obtained ABS material is 33.2KJ / m 2 , low temperature impact strength is 15.8KJ / m 2 , good low temperature resistance and high impact strength.
[0070] Examples 23-35
[0071] Preparation of benzoxazine flame retardants:
[0072] 3 mol of aniline, 3.0 mol of 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene (phenolic hydroxyl group), and 6 mol of polyformaldehyde were stirred and mixed in a beaker at room temperature to obtain a mixed solution; 1 / 10 of the mixed solution was added to a 1000 ml flask, the temperature was raised to 70° C., and the reaction was carried out for 10 minutes to obtain a reaction solution 1; 1 / 10 of the second batch of the mixed solution was added to the reaction solution 1, and the reaction was carried out for 10 minutes to obtain a reaction solution 2; the remaining mixed solution was added, and after the raw materials were added, the reaction temperature was maintained at 110° C., and the reaction was carried out under reflux for 20 minutes to obtain a reaction system; the reaction system was heated to 130° C., stirred and refluxed for 30 minutes to evaporate water, centrifuged, and vacuum dried at 80° C. for 2 hours to obtain a benzoxazine flame retardant.
[0073] The preparation method of the modified flame retardant comprises the following steps:
[0074] Calcine graphene in a muffle furnace for 5 hours to obtain fired graphene; add the fired graphene to a 10% hydrochloric acid solution, heat and reflux at 50°C for 10 hours, centrifuge and wash, and freeze-dry to obtain acidified graphene; add 10 parts of the acidified graphene to a three-necked flask, dissolve it in 100 ml of a mixed solution of ethanol and water (V alcohol: V water = 5:1) to obtain a mixed solution, adjust the mixed solution to weak acidity with glacial acetic acid, ultrasonically disperse for 30 minutes, add 5 parts of KH-570, and stir and react for 6 hours in a water bath at 85°C to obtain modified graphene; place the modified graphene in a beaker, add anhydrous ethanol, stir and disperse evenly, and obtain a dispersion; add a halogen-free flame retardant to the dispersion, transfer it to a reactor, stir and react for 2 hours at 80°C, separate and centrifuge, and vacuum dry to obtain a graphene-loaded halogen-free flame retardant;
[0075] The preparation of ABS material refers to the preparation method and parameter conditions of Example 1, and the differences are shown in Table 3.
[0076] Comparative Example 4 The preparation method and parameter conditions are the same as those of Example 15, except that no benzoxazine flame retardant is added.
[0077] Comparative Example 5 The preparation method and parameter conditions are the same as those of Example 15, except that triphenyl phosphate is not added.
[0078] Example 36 Flame retardant performance test
[0079] The ABS materials prepared in Examples 23-35 and Comparative Examples 4-5 were sampled, and the sample size was 150 mm×6.5 mm×3 mm. The limiting oxygen index test was performed in accordance with GB / T2406-1993. The test results are shown in Table 3.
[0080] Table 3 Flame retardant performance test of Examples 23-35 and Comparative Examples 4-5
[0081]
[0082] The results in Table 3 show that the limiting oxygen index of the ABS materials prepared by using a single flame retardant in Comparative Examples 4 and 5 is significantly lower than that in Examples 23-35. When BOZ is added alone, although it has good heat resistance, it cannot achieve the desired flame retardant effect due to its low crosslinking density. ABS itself is difficult to form carbon. When TPP is added alone, it is difficult to form a carbon layer due to the lack of a carbon source, which plays a role in stopping combustion. At the same time, TPP is easy to volatilize at low temperatures, further affecting the flame retardant effect. The results of Comparative Examples 23-28 show that the use of organic phosphorus flame retardants in combination with other flame retardants can effectively improve the flame retardant properties of ABS materials, and the limiting oxygen index can reach more than 30%. Due to the good carbonization of BOZ, it can cooperate with the organic phosphorus flame retardant to participate in the flame retardant process. When BOZ is open-loop cured, A cross-linked network is formed to inhibit the volatilization of organic phosphorus. At the same time, the phenolic hydroxyl groups formed during the ring-opening curing process react with the phosphoric acid and polymetaphosphoric acid generated by the decomposition of organic phosphorus at high temperature to undergo an esterification reaction, so that the cross-linking density of the benzoxazine resin is increased, and a dense carbon layer is formed on the surface of the combustion product to achieve a better flame retardant effect; compared with the results of Example 23 and Examples 29-31, it can be seen that with the increase in the amount of flame retardant, the flame retardant properties of the ABS material gradually increase, but the compatibility of the excessive BOZ with the system decreases, thereby reducing the mechanical properties of the ABS; the results of Examples 23 and Examples 32-35 show that with the increase in the amount of BOZ, the limiting oxygen index shows a trend of first increasing and then decreasing, further indicating that the excessive use of benzoxazine flame retardants reduces the interfacial compatibility between ABS material molecules and reduces the flame retardant properties of the material. Comprehensive Table 3 results show that the use of BOZ / TPP as a flame retardant compound, the control of the amount of flame retardant and the proportion of components, the limiting oxygen index of the obtained ABS material is 35.6%, and has significantly improved flame retardant properties. Embodiment 37
[0083] Prepare 1 mol / L cobalt nitrate hexahydrate solution and 0.5 mol / L magnesium nitrate hexahydrate solution, add them to a flask and stir evenly to obtain a mixed metal solution; prepare 2.4 mol / L sodium hydroxide solution and 1 mol / L sodium carbonate solution, add them to a flask, stir evenly to obtain a mixed alkali solution; slowly add 10 ml of the mixed metal solution and 10 ml of the mixed alkali solution into a rotating liquid film reactor at a speed of 3000 rpm, and stir for 20 minutes to obtain a nucleation slurry; transfer the nucleation slurry to a flask, heat it to 100°C and reflux for 6 hours to obtain a reactant; wash the reactant with deionized water, rinse with ethanol, adjust the pH to neutral, and vacuum dry it at 60°C for 24 hours to obtain a smoke suppressant. The surface morphology of the obtained smoke suppressant is shown in the figure below. Figure 1 shown.
[0084] The preparation method of ABS material refers to Example 15.
[0085] Examples 38-45 Refer to the preparation method and parameter conditions of Example 37, with the differences as shown in Table 4.
[0086] Comparative Example 6 The preparation method and parameter conditions are the same as those of Example 37, except that no smoke suppressant is added.
[0087] Comparative Example 7 The preparation method and parameter conditions are the same as those of Example 37, except that magnesium hydroxide is added as a smoke suppressant.
[0088] Example 46 Smoke Density Test
[0089] Referring to GB / T8627-1999, the edge banding strips prepared in Examples 37-45 and Comparative Examples 6-7 were tested for smoke suppression performance using low-smoke halogen-free flame-retardant ABS material using a smoke density test box produced by Kunshan Modis. The test mode was ISO5659, the distance from the surface of the heat flux meter to the ground of the radiation cone was 25 mm, the test time was set to 800 s, the sample size was controlled to 7.5 cm × 7.5 cm × 1 mm, the sample weight was controlled to 7.5 ± 0.1 g, and the smoke density results are shown in Table 4.
[0090] Table 4 Smoke density test of Examples 37-45 and Comparative Examples 6-7
[0091]
[0092] like Figure 1The results show that the smoke suppressant has a flaky particle-like appearance, concentrated particle distribution, small size, and clear morphology, and a typical two-dimensional layered double metal hydroxide hexagonal flaky structure can be observed. The results in Table 4 show that the total smoke release of the ABS material obtained in Comparative Example 6 without adding a smoke suppressant is significantly increased compared to Examples 37-45, and smoke is released during the combustion process; Comparative Example 7 uses magnesium hydroxide inorganic material as a smoke suppressant, and the total smoke release is reduced compared to Comparative Example 6, and the smoke release is reduced. However, the addition of inorganic materials leads to reduced compatibility, which affects the smoke suppression effect of the material; the results of Examples 37-41 show that the total smoke release first decreases and then increases with the increase of the Co / Mg ratio. With the increase of the molar ratio of the metal solution, the total smoke release of the ABS material changes significantly. The crystallinity of the obtained smoke suppressant changes with the different molar ratios; with the increase of the molar amount of the cobalt nitrate hexahydrate solution, the crystallinity of the smoke suppressant decreases, resulting in its agglomeration phenomenon, a larger secondary particle size, an irregular shape, and a rough surface, all of which may reduce its content in the ABS material. dispersibility, increasing the total amount of smoke released; through the results of Examples 37 and 42-45, it can be seen that with the increase of the content of smoke suppressant, the total amount of smoke released by ABS material shows a trend of gradually decreasing. After the smoke suppressant is blended with ABS, the amount of residual carbon in the material increases, and the residual carbon presents an irregular layered structure. This structure can not only block the entry and exit of harmful gases and heat, but also complicate the propagation path of the gas, thereby inhibiting the internal and external exchange of the gas, and at the same time has the effect of promoting carbonization. More carbon is fixed in the residual carbon, and the stable carbon layer reduces the release of combustible molecules such as aromatic compounds, related carbonyl compounds, and carbon monoxide, and the total amount of smoke released decreases. Secondly, during the thermal decomposition process, the smoke suppressant can release water vapor and carbon dioxide. These gases help to reduce the combustion temperature of the composite material and dilute the combustible gas in the surrounding environment, thereby playing a flame retardant and smoke suppression effect. Figure 1 The results in Table 5 show that by controlling the molar ratio of the metal solution and the amount of smoke suppressant, the smoke density of the ABS material obtained is 235, which meets the international environmental protection standards and reduces the smoke release.
[0093] Examples 47-54
[0094] The preparation method of the modified flame retardant comprises the following steps:
[0095] Calcine graphene in a muffle furnace for 5 hours to obtain fired graphene; add the fired graphene to a 10% hydrochloric acid solution, heat and reflux at 50°C for 10 hours, centrifuge and wash, and freeze-dry to obtain acidified graphene; add 10 parts of the acidified graphene to a three-necked flask, dissolve it in 100 ml of a mixed solution of ethanol and water (V alcohol: V water = 5:1) to obtain a mixed solution, adjust the mixed solution to weak acidity with glacial acetic acid, ultrasonically disperse for 30 minutes, add 5 parts of silane coupling agent, and stir and react for 6 hours in a water bath at 85°C to obtain modified graphene; place the modified graphene in a beaker, add anhydrous ethanol, stir and disperse evenly, and obtain a dispersion; add a halogen-free flame retardant to the dispersion, transfer it to a reactor, stir and react for 2 hours at 80°C, separate and centrifuge, and vacuum dry to obtain a graphene-loaded halogen-free flame retardant;
[0096] The preparation of ABS material refers to the preparation method and parameter conditions of Example 1, and the differences are shown in Table 5.
[0097] Comparative Example 8 The preparation method and parameter conditions are the same as those of Example 38, except that no modified graphene is added.
[0098] Comparative Example 9 The preparation method and parameter conditions are the same as those of Example 38, except that unmodified graphene is added.
[0099] Example 55 Heat resistance test
[0100] The thermal stability of the low-smoke, halogen-free flame-retardant ABS materials for edge banding prepared in the above Examples 47-54 and Comparative Examples 8-9 was tested. The ABS materials prepared in each Example were subjected to thermogravimetric analysis, with the temperature range from 30-600°C and the heating rate of 10°C / min. The initial decomposition temperature and the residual carbon rate were recorded. The results are shown in Table 5. The initial decomposition temperature and the residual carbon rate of Example 49 and Examples 51-54 are shown in Table 5. Figure 2 shown.
[0101] Table 5 Heat resistance test of Examples 47-54 and Comparative Examples 8-9
[0102]
[0103] The results in Table 5 show that the initial decomposition temperature of the ABS material prepared by not adding the modified graphene-loaded halogen-free flame retardant in Comparative Example 8 is 298°C, which shows a significantly reduced heat resistance compared to Examples 47-54. Since no graphene loading is added, the halogen-free flame retardant decomposes at a higher temperature, resulting in a decrease in the flame retardancy of the ABS, which cannot prevent combustion. The increase in temperature further consumes the material, and the final carbon residue rate is low. In Comparative Example 9, unmodified graphene-loaded flame retardant is used, and the heat resistance is improved compared to Comparative Example 8. However, the compatibility of graphene with ABS materials is poor. Agglomeration occurs in the material structure, further reducing the heat resistance of the material. At the same time, the particle structure formed by agglomeration wraps the flame retardant component, further reducing the flame retardancy of the material. The results of Examples 47-50 show that since KH-570 forms a silanol structure under acidic conditions, it can form a bond with the acidified graphene surface, and at the same time, the exposed olefin bond at the other end can undergo graft polymerization with the ABS main chain, and the compatibility of the ABS material is further improved under the action of the plasticizer, while the terminal groups of other silane coupling agents are polar groups, which reduce the compatibility with the ABS material and deteriorate the heat resistance. Figure 2 The results of Examples 49 and 51-54 show that as the amount of modified graphene increases, the thermal decomposition temperature and residual carbon rate of ABS materials gradually increase and tend to remain constant. An appropriate amount of modified graphene as a matrix, with its high surface area and special crystal structure, can load halogen-free flame retardants, promote flame conduction and heat release, thereby achieving flame retardancy. At the same time, loading halogen-free flame retardants can avoid rapid decomposition of flame retardants at high temperatures, avoid excessively high temperatures leading to reduced flame retardant properties, and further improve the heat resistance of ABS materials. Figure 2 From the results in Table 5, it can be seen that by modifying graphene with silane coupling agent and controlling the dosage, the initial decomposition temperature of the low-smoke halogen-free flame-retardant ABS material is 364°C and the residual carbon rate is 51.2%.
[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding, characterized in that: The preparation method of the low-smoke halogen-free flame-retardant ABS material comprises the following steps: 20-40 parts of emulsion copolymer, 70-100 parts of bulk ABS, graphene-loaded halogen-free flame retardant, 10-25 parts of toughening agent, 2 parts of antioxidant 1010, and 2-10 parts of smoke suppressant are placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain a dry material; the dry material is added to a high-speed mixer and stirred at 500r / min for 30 minutes, and mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder for melt blending and extrusion, cooled, and pelletized to obtain pellets; the pellets are vacuum dried at 85°C for 5 hours and then injection molded by an injection molding machine to obtain the low-smoke halogen-free flame retardant ABS material; The emulsion copolymer is prepared by emulsifying isoprene, styrene and acrylonitrile in a weight ratio of 17:61:22; The smoke suppressant is prepared by a nucleation-crystallization isolation method using a cobalt nitrate hexahydrate solution and a magnesium nitrate hexahydrate solution; The graphene-loaded halogen-free flame retardant is prepared by adding 5-15 parts of modified graphene and 8-18 parts of halogen-free flame retardant, dispersing them in anhydrous ethanol, and stirring and reacting them at 80° C. for 2 hours. The modified graphene is prepared by acidifying graphene and modifying it with a silane coupling agent; The halogen-free flame retardant is prepared by mixing flame retardant 1 and flame retardant 2 in a ratio of 1-3:1-3; The toughening agent is selected from one of styrene-butadiene-styrene block copolymer, ethylene-vinyl acetate copolymer, styrene-butadiene rubber, butadiene rubber, and silicone rubber; The flame retardant 1 is selected from one of benzoxazine flame retardants, polyvinyl chloride, polyphenylene ether, and phenolic resin; the flame retardant 2 is selected from one of triphenyl phosphate, ammonium metaphosphate, and resorcinol; The silane coupling agent is selected from one of 3-aminopropyltriethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, methacryloxypropyltriethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
2. The method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding according to claim 1, characterized in that: The bulk ABS is selected from one of ABS 8391, ABS 3504, ABS 8434, and ABS 275.
3. The method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding according to claim 1, characterized in that: The preparation method of the benzoxazine flame retardant comprises the following steps: Aniline, 1,2-diphenyl-1,2-di(4-hydroxyphenyl)ethylene and polyformaldehyde are stirred and mixed in a beaker at room temperature to obtain a mixed solution; 1 / 10 of the mixed solution is added to a 1000 ml flask, the temperature is raised to 70°C, and the reaction is carried out for 10 minutes to obtain a reaction solution 1; 1 / 10 of the second batch of the mixed solution is added to the reaction solution 1, and the reaction is carried out for 10 minutes to obtain a reaction solution 2; the remaining mixed solution is added, and after the raw materials are added, the reaction temperature is maintained at 110°C, and the reaction is carried out under reflux for 20 minutes to obtain a reaction system; the reaction system is heated to 130°C, stirred and refluxed for 30 minutes to evaporate water, centrifuged, and vacuum dried at 80°C for 2 hours to obtain the benzoxazine flame retardant.
4. The method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding according to claim 1, characterized in that: The preparation method of the smoke suppressant comprises the following steps: The cobalt nitrate hexahydrate solution and the magnesium nitrate hexahydrate solution are prepared, added to a flask and stirred evenly to obtain a mixed metal solution; sodium hydroxide solution and sodium carbonate solution are prepared, added to a flask, and stirred evenly to obtain a mixed alkali solution; the mixed metal solution and an equal volume of the mixed alkali solution are slowly added into a rotating liquid film reactor at a speed of 3000 rpm, and stirred for 20 minutes to obtain a nucleation slurry; the nucleation slurry is transferred to a flask, heated to 100°C and refluxed for 6 hours to obtain a reactant; the reactant is washed with deionized water, rinsed with ethanol, the pH is adjusted to neutral, and vacuum dried at 60°C for 24 hours to obtain the smoke suppressant.
5. The method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding according to claim 1, characterized in that: The molar concentration ratio of the cobalt nitrate hexahydrate solution to the magnesium nitrate hexahydrate solution is 1-4:1-2.
6. The method for preparing a low-smoke, halogen-free, flame-retardant ABS material for edge banding according to claim 1, characterized in that: The preparation method of the graphene-loaded halogen-free flame retardant comprises the following steps: The graphene is placed in a muffle furnace and calcined for 5 hours to obtain fired graphene; the fired graphene is added to a 10% hydrochloric acid solution and heated to reflux at 50°C for 10 hours, centrifuged and washed, and freeze-dried to obtain acidified graphene; the acidified graphene is added to a three-necked flask, and dissolved in a mixed solution of ethanol and water to obtain a mixed solution, the mixed solution is adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, the silane coupling agent is added, and the mixture is stirred and reacted for 6 hours in a water bath at 85°C to obtain the modified graphene; the modified graphene is placed in a beaker, anhydrous ethanol is added, stirred and dispersed evenly, to obtain a dispersion; the halogen-free flame retardant is added to the dispersion, and the mixture is transferred to a reactor and stirred and reacted at 80°C for 2 hours, separated and centrifuged, and vacuum dried to obtain the graphene-loaded halogen-free flame retardant.
7. A low-smoke, halogen-free, flame-retardant ABS material for edge banding, characterized in that: The low-smoke halogen-free flame-retardant ABS material comprises an emulsion copolymer, a bulk ABS, modified graphene, a halogen-free flame retardant, a toughening agent, an antioxidant 1010, and a smoke suppressant; the low-smoke halogen-free flame-retardant ABS material is prepared by the preparation method described in any one of claims 1 to 6; the tensile strength of the ABS material is 55 MPa, and the elongation at break is 31.5%; the impact strength of the ABS material at 23±2°C is 33.2 KJ / m 2 , the impact strength at -30±2℃ is 15.8KJ / m 2 ; The limiting oxygen index of the ABS material is 35.6%; The smoke density of the ABS material is 235; The initial decomposition temperature of the ABS material is 364°C, and the residual carbon rate is 51.2%.
Citation Information
Patent Citations
Low-smoke halogen-free flame retardant PC / ABS alloy and preparation method thereof
CN101591468B
Low-smoke halogen-free flame-retardant elastomer sheath material for rail vehicle cables and preparation method thereof
CN104031306A
Preparation method of PCR high-impact PC / ABS automotive interior material
CN113913007A